Impact of Educational Sessions Based on Thelen’s Model on Learning Basic Basketball Skills among Secondary School Students - Luay Jaleel Manshad; Zaid Abdulzahra Hamidi (Journal of Education and Sport Science, 2026)
Objectives: This study aimed to examine the effect of educational sessions based on Thelen’s model on learning basic basketball skills among secondary school students. Materials and Methods: This study used an experimental design with two equivalent groups and pre-test–post-test measurements. The participants were 49 fifth-grade science students from Daabal Al-Khaza’i Secondary School for Boys. After exclusions, the main sample consisted of two groups: an experimental group and a control group, each consisting of 16 students. The experimental group was taught using educational sessions based on Thelen’s model, while the control group was taught using the traditional method. The program consisted of eight weekly sessions focused on lay-up shooting and jump shooting. Data were analyzed using SPSS version 23. Results: Both groups showed significant improvement from pre-test to post-test in lay-up shooting and jump shooting. However, the experimental group achieved better post-test results than the control group. In lay-up shooting, the experimental group obtained a post-test mean of 23.954, compared with 21.396 in the control group. In jump shooting, the experimental group obtained a post-test mean of 20.795, compared with 17.651 in the control group. Conclusions: Educational sessions based on Thelen’s model were more effective than the traditional method in improving lay-up shooting and jump shooting among secondary school students. The model encouraged cooperation, group inquiry, active participation, and reflective learning, making it suitable for basketball instruction in physical education classes.